History rising - Dijkman, Marjolijn; Fernie, Jes; Watkins, Jonathan; Fijalkowski, Krzysztof (Eindhoven : Onomatopee, 2015)
History Rising is an engaging study of museum display. Viewers and participants are invited to reconsider their view of history by looking at the mechanisms museums put in place to create a sense of order and hierarchy within their collections. By distancing museum objects from their support structures History Rising forms a critique of the assumptions that are made about how things are positioned, who chooses to display them, and how the social, political and aesthetic choices that are made in the process dictate the language of display. Dijkman’s newly produced sculptures propose strange and fantastical juxtapositions, alleviate objects from the weight of history and create links with modernism, the heritage industry and the aesthetics of sci-fi.
boek